Using molecular gut content analysis to identify key predators in a classical weed biological control system: a study with Neomusotima conspurcatalis (Lepidoptera: Crambidae) - Ian M. Jones; Paul T. Madeira; J. Zizah Blair; Ellen C. Lake (BioControl, 2021)

Application of predator-associated cues to control small brown planthoppers: non-consumptive effects of predators suppress the pest population - Jian Wen; Takatoshi Ueno (BioControl, 2021)

Bacterial communities in predatory mites are associated with species and diet types - Jingyi Yan; Bo Zhang; Guiting Li; Xuenong Xu (BioControl, 2021)

Density-dependent interactions between the nematode Meloidogyne incognita and the biological control agent Agasicles hygrophila on invasive Alternanthera philoxeroides and its native congener Alternantera sessilis - Hairong Qin; Wenfeng Guo; Xiaoqiong Li (BioControl, 2021)

The effect of insecticide application by dropleg sprayers on pollen beetle parasitism in oilseed rape - Johannes Hausmann; Udo Heimbach; Michael Rostás; Meike Brandes (BioControl, 2021)
Dropleg sprayers apply pesticides below the flower horizon of oilseed rape plants and thus reduce unwanted side effects on pollinating insects. Whether this technique benefits parasitoids of seed and pollen feeding insect pests has not been studied earlier. To answer this question, we first assessed the vertical distribution of pests and parasitoids using a portable aspirator. In addition, parasitism rates of pollen beetle, Brassicogethes aeneus Fabricius (Coleoptera: Nitidulidae) , by the larval parasitoid Tersilochus heterocerus Thomson (Hymenoptera: Ichneumonidae) were compared in conventional and dropleg sprayed fields over four years (2016–2019), using the neonicotinoids thiacloprid and acetamiprid. Our results show that seed and pollen feeders were mainly found in the flowering canopy, while the predominant location of parasitoids was species-specific. Among pollen beetle parasitoids, Phradis interstitialis Thomson (Hymenoptera: Ichneumonidae) was more abundant below flowering canopy (63% of total catch), whereas T. heterocerus was mainly caught in the flowering canopy (84% of total catch). In the spraying experiments, average parasitism rates of pollen beetles by T. heterocerus ranged between 55 and 82% in the untreated controls. In the dropleg spray treatments, parasitism rates did not differ significantly from control levels, with the exception of thiacloprid application in 2019. In contrast, conventional spray applications resulted in a reduction of parasitism rates by up to 37% compared to the control for at least one of the insecticides in three out of four years. The impact of conventional application differed between years, which may be explained by the temporal coincidence between spray application and the immigration of parasitoids into the crop. We conclude that dropleg spraying exerts lower non-target effects on the main biological control agent of pollen beetle.

The prospects for cryopreservation of noctuid eggs in the mass production of Trichogramma spp. - Magda F. Paixão; Tamara A. Takahashi; Guilherme L. Sassaki; Luís A. Foerster (BioControl, 2021)

Evaluation of four artificial diets on demography parameters of Neoseiulus barkeri - Ya-Ying Li; Jin-Ge Yuan; Ming-Xiu Liu; Zi-Hui Zhang; Hai-Wei Zhou; Huai Liu (BioControl, 2021)

Contrasting host: parasitoid synchrony drives differing levels of biocontrol by two introduced Microctonus spp. in northern New Zealand pastures - Philippa Gerard; Derrick Wilson; Martin Upsdell (BioControl, 2021)

Host specificity testing of Pauesia nigrovaria (Hymenoptera: Braconidae: Aphidiinae) for classical biological control of Tuberolachnus salignus (Hemiptera: Aphididae: Lachninae) in New Zealand - Stephanie Sopow; Carl Wardhaugh; Rebecca Turner; Belinda Gresham; Roanne Sutherland; Georgia Woodall; Toni Withers (BioControl, 2021)

Enhanced expression of DNA methyltransferase 1-associated protein1 gene thermotolerance in a high-temperature acclimated predatory mite Neoseiulus barkeri - Ya-Ying Li; Chuan-Bei Tian; Yi-Xia Wu; Tian-Di Niu; Hao Wang; Wen-Hui Fan; Huai Liu (BioControl, 2021)

Loop-mediated isothermal amplification based identification of entomopathogenic nematodes Heterorhabditis spp. and Steinernema spp. from soil DNA - Gagandeep Singh; Amit Ahuja; Uma Rao; Vishal Singh Somvanshi (BioControl, 2021)

Mutual interference in the mass-reared fruit fly parasitoid, Diachasmimorpha longicaudata (Hymenoptera: Braconidae) - Patricia López; Daniel Rosales; Salvador Flores; Pablo Montoya (BioControl, 2021)

Specialized soil types affect host acceptability and performance of weed biocontrol candidates: implications for host specificity assessments - Sujan Panta; Philip Weyl; Sanford D. Eigenbrode; Bradley L. Harmon; Mark Schwarzländer (BioControl, 2021)

Suitability for classical biological control of Hedychium coronarium in Argentina - Fernando Mc Kay; Djamila Djeddour; Alejandro Sosa; Guillermo Cabrera Walsh; Freda E. Anderson; Andrés Sánchez-Restrepo (BioControl, 2021)

Natural enemies associated with Tuta absoluta and functional biodiversity in vegetable crops - Judit Arnó; Paula Molina; Yahana Aparicio; Carmen Denis; Rosa Gabarra; Jordi Riudavets (BioControl, 2021)

Tachinids associated with lepidopteran pests in agricultural crops in south-central region of Goiás, Brazil - Igor Daniel Weber; Welinton Ribamar Lopes; Letícia Chiara Baldassio de Paula; Karina Cordeiro Albernaz-Godinho; Cecilia Czepak (BioControl, 2021)

Non-consumptive effects of Encarsia formosa on the reproduction and metabolism of the whitefly Bemisia tabaci - Ze-Yun Fan; Zhan-Peng Zhu; Jing Peng; Xin-Yi Chen; Zi-Tong Lu; Hui-Peng Pan; Bao-Li Qiu (BioControl, 2021)

Genetic improvement of spinosad resistance in the biocontrol agent Orius laevigatus - Virginia Balanza; José Enrique Mendoza; Dina Cifuentes; Pablo Bielza (BioControl, 2021)

Effect of tomato genotypes with varying levels of susceptibility to Tetranychus evansi on performance and predation capacity of Phytoseiulus longipes - Patrice Jacob Savi; Gilberto José de Moraes; Daniel Júnior de Andrade (BioControl, 2021)

Screening for effective microbial consortia against Fusarium wilt of cape gooseberry (Physalis peruviana) - L. F. Izquierdo-García; A. M. Cotes; C. A. Moreno-Velandia (BioControl, 2021)

Tracking the movement of Nesidiocoris tenuis among banker plants and crops in a tomato greenhouse by DNA markers of host plants - Ryohei Nakano; Norihide Hinomoto (BioControl, 2021)

Intraspecific variation in biocontrol traits in Mastrus ridens (Hymenoptera: Ichneumonidae) laboratory populations - Tania Zaviezo; Alda Romero; Felipe Calleja; Cristóbal Calvo; Roberto Osorio; Fernando Casanoves; Paula Irles (BioControl, 2021)

Provision of astigmatid mites as supplementary food increases the density of the predatory mite Amblyseius swirskii in greenhouse crops, but does not support the omnivorous pest, western flower thrips - Fatemeh Pirayeshfar; Seyed Ali Safavi; Hamid Reza Sarraf Moayeri; Gerben J. Messelink (BioControl, 2021)
Astigmatid mites can be used as prey for mass rearing of phytoseiid predators, but also as a supplemental food source to support predator populations in crops. Here we evaluated the potential of six species of astigmatid mites (living or frozen) as alternative food for the predatory mite Amblyseius swirskii Athias-Henriot in greenhouse crops. All prey mites tested were suitable for predator oviposition. In general, oviposition was greater when prey mites were reared on dog food with yeast than when they were reared on wheat bran with yeast. Amongst prey items provided as frozen diet, larvae of Thyreophagus entomophagus (Laboulbene), Acarus siro L. and Lepidoglyphus destructor (Schrank) that had been reared on dog food with yeast, resulted in the highest oviposition rates of A. swirskii . T. entomophagus larvae as frozen diet resulted in the shortest preimaginal developmental time of A. swirskii . On chrysanthemum plants, we found that the greatest increase in predator density occurred when living mites of T. entomophagous were used as a food source. This increase was greater than when predators were fed cattail pollen, a commonly used supplemental food. Effects on predators of providing living A. siro and L. destructor , or frozen larvae of T. entomophagous as food, were comparable with provision of pollen. Use of supplemental food in crops can be a risk if it is also consumed by omnivorous pests such as western flower thrips, Frankliniella occidentalis Pergande. However, we showed that both frozen and living mites of T. entomophagous were unsuitable for thrips oviposition. Hence, we believe that provision of prey mite species increases A. swirskii density, supporting biological control of thrips and other pests in greenhouse crops.

Nutritional niche overlap analysis as a method to identify potential biocontrol fungi against trunk pathogens - C. M. Wallis (BioControl, 2021)

Efficacy of Wickerhamomyces anomalus yeast in the biocontrol of blue mold decay in apples and investigation of the mechanisms involved - Lina Zhao; Yuanjian Wang; Solairaj Dhanasekaran; Zhipeng Guo; Shangjian Chen; Xiaoyun Zhang; Hongyin Zhang (BioControl, 2021)

Eriophyid mite Floracarus perrepae readily colonizes recovering invasive vine Lygodium microphyllum following herbicide treatment - Aaron S. David; Jonathan S. Glueckert; Stephen F. Enloe; Andrea Carmona Cortes; Anwar A. Abdel-Kader; Ellen C. Lake (BioControl, 2021)

Biological control of strawberry crown rot, root rot and grey mould by the beneficial fungus Aureobasidium pullulans - Mudassir Iqbal; Maha Jamshaid; Muhammad Awais Zahid; Erik Andreasson; Ramesh R. Vetukuri; Johan A. Stenberg (BioControl, 2021)
Utilization of biocontrol agents is a sustainable approach to reduce plant diseases caused by fungal pathogens. In the present study, we tested the effect of the candidate biocontrol fungus Aureobasidium pullulans (De Bary) G. Armaud on strawberry under in vitro and in vivo conditions to control crown rot, root rot and grey mould caused by Phytophthora cactorum (Lebert and Cohn) and Botrytis cinerea Pers, respectively. A dual plate confrontation assay showed that mycelial growth of P. cactorum and B. cinerea was reduced by 33–48% when challenged by A. pullulans as compared with control treatments. Likewise, detached leaf and fruit assays showed that A. pullulans significantly reduced necrotic lesion size on leaves and disease severity on fruits caused by P. cactorum and B. cinerea . In addition, greenhouse experiments with whole plants revealed enhanced biocontrol efficacy against root rot and grey mould when treated with A. pullulans either in combination with the pathogen or pre-treated with A. pullulans followed by inoculation of the pathogens. Our results demonstrate that A. pullulans is an effective biocontrol agent to control strawberry diseases caused by fungal pathogens and can be an effective alternative to chemical-based fungicides.

Efficacy of Entomopathogenic fungus Aspergillus nomius against Dolichoderus thoracicus - Wei-Jiun Lin; Ming-Chung Chiu; Chung-Chi Lin; Yuan-Kai Chung; Jui-Yu Chou (BioControl, 2021)

Do the beneficial fungi manage phytosanitary problems in the tea agro-ecosystem? - Abhay K. Pandey; Bhabesh Deka; Richa Varshney; Evelyn Chepkirui Cheramgoi; Azariah Babu (BioControl, 2021)

Impact of relative humidity and water availability on the life history of the predatory mite Amblyseius swirskii - Phyu Phyu San; Midori Tuda; Masami Takagi (BioControl, 2021)

Potential of the predatory mite Amblydromalus zannoui to control pest mites on Jatropha curcas - Valdirene Coutinho Miranda; Emiliano Brandão de Azevedo; Wilton Pires da Cruz; Sofía Jiménez Jorge; Marçal Pedro-Neto; Raphael de Campos Castilho; Marie-Stéphane Tixier; Gilberto José de Moraes; Renato Almeida Sarmento (BioControl, 2021)

Entomopathogenic nematodes and fungi to control Hyalesthes obsoletus (Hemiptera: Auchenorrhyncha: Cixiidae) - Abdelhameed Moussa; Michael Maixner; Dietrich Stephan; Giacomo Santoiemma; Alessandro Passera; Nicola Mori; Fabio Quaglino (BioControl, 2021)
Hyalesthes obsoletus Signoret (Hemiptera: Auchenorrhyncha: Cixiidae) is a univoltine, polyphagous planthopper that completes its life cycle, including the subterranean nymph cryptic stage, on herbaceous weeds. In vineyards, it can transmit ‘ Candidatus Phytoplasma solani’, an obligate parasitic bacterium associated with bois noir (BN) disease of grapevine, from its host plants to grapevine when occasionally feeding on the latter. The main disease management strategies are based on vector(s) control. Insecticide treatments on grapevine canopy are completely inefficient on H. obsoletus , due to its life cycle. Consequently, control of this planthopper focuses on the nymphs living on the roots of their host plants. Such practices, based on herbicide application and/or weed management, can reduce vector density in the vineyard but can impact the environment or may not be applicable, highlighting the necessity for alternative strategies. In this study, the efficacy of entomopathogenic nematodes (EPNs; Steinernema carpocapsae , S. feltiae , Heterorhabditis bacteriophora ) and fungi (EPFs; Beauveria bassiana , Metarhizium anisopliae , Isaria fumosorosea , Lecanicillium muscarium ) against H. obsoletus nymphs (EPNs) and adults (EPNs and EPFs) was assessed under laboratory and greenhouse conditions. The majority of examined EPNs and EPFs were able to kill H. obsoletus exhibiting a range of effectiveness. S. carpocapsae (among EPNs) and I. fumosorosea (among EPFs) were found to be the most effective biocontrol agents in all trials carried out. Advantages and limitations of such promising biocontrol agents were discussed. Ecological competency and conditions that can impede or enhance the EPNs and EPFs performance should be investigated to optimize their performance under field conditions.

Correction to: Cleome hassleriana plants fully support the development and reproduction of Nesidiocoris tenuis - Ryohei Nakano; Taiki Morita; Yuta Okamoto; Ayaka Fujiwara; Takehiko Yamanaka; Tetsuya Adachi-Hagimori (BioControl, 2021)

Effects of temperature and relative humidity on Aflatoxin B1 reduction in corn grains and antagonistic activities against Aflatoxin-producing Aspergillus flavus by a volatile organic compound-producing yeast, Kwoniella heveanensis DMKU-CE82 - Sopin Jaibangyang; Rujikan Nasanit; Savitree Limtong (BioControl, 2021)

Cleome hassleriana plants fully support the development and reproduction of Nesidiocoris tenuis - Ryohei Nakano; Taiki Morita; Yuta Okamoto; Ayaka Fujiwara; Takehiko Yamanaka; Tetsuya Adachi-Hagimori (BioControl, 2021)

Age and parasitism status of Tuta absoluta eggs alter the foraging responses of the predator Nabis pseudoferus - Marzieh Mohammadpour; J. P. Michaud; Mojtaba Hosseini; Javad Karimi; Vahid Hosseininaveh (BioControl, 2021)

Plant defense responses triggered by phytoseiid predatory mites (Mesostigmata: Phytoseiidae) are species-specific, depend on plant genotype and may not be related to direct plant feeding - Joaquín Cruz-Miralles; Marc Cabedo-López; Michela Guzzo; Meritxell Pérez-Hedo; Víctor Flors; Josep A. Jaques (BioControl, 2021)
Zoophytophagous arthropods can elicit plant defense responses affecting potential prey beyond predation. Phytophagy prevails as the main trigger for these responses, as in the case of Euseius stipulatus (Athias-Henriot) (Mesostigmata: Phytoseiidae), a predator occurring in citrus. Because other triggers cannot be excluded, our aim was to examine whether other phytoseiids co-occurring with E. stipulatus but not engaged in plant feeding [ Neoseiulus californicus (McGregor) and Phytoseiulus persimilis Athias-Henriot] could induce similar responses (in terms of herbivore induced plant volatiles, HIPVs, and main defensive pathways), and how these affected the behavior of conspecifics and the shared prey, Tetranychus urticae Koch (Prostigmata: Tetranychidae). N. californicus triggered plant genotype-specific defense responses, including the production of different HIPVs compared to clean plants. However, we could not observe these effects for P. persimilis . T. urticae avoided better protected plants, because of stronger direct or indirect defense. As plants with weaker direct defense levels should offer higher prey densities, and those harboring conspecific predators represent higher risk of cannibalism, predators were expected to behave similarly. However, they did not. Our results demonstrate that plant defense triggered by phytoseiids is species-specific, depend on plant genotype and can be triggered by non-feeding activities. As N. californicus is a highly efficient predator used worldwide, further studies with this species are needed. Likewise, cineol, one of the volatiles identified in the blends triggered by this phytoseiid, could be used to manipulate the prey. These studies could pave the way for a more efficient use of phytoseiids in agroecosystems.

The invasive stink bug Halyomorpha halys affects the reproductive success and the experience-mediated behavioural responses of the egg parasitoid Trissolcus basalis - Ezio Peri; Maria Cristina Foti; Letizia Martorana; Antonino Cusumano; Stefano Colazza (BioControl, 2021)

Potential inter-guild interactions to enhance biological control of Bactericera cockerelli on tomatoes: a laboratory and cage study - Emiliano R. Veronesi; Oluwashola Olaniyan; Howard London; David J. Saville; Stephen D. Wratten (BioControl, 2021)

Establishment of the predator Laricobius nigrinus, introduced as a biological control agent for hemlock woolly adelgid in Virginia, USA - Carrie S. Jubb; Thomas J. McAvoy; Kari E. Stanley; Ariel R. Heminger; Scott M. Salom (BioControl, 2021)

Host discrimination of a larval parasitoid: the quick movement of Microplitis demolitor - Shun-ichiro Takano; Nancy A. Schellhorn (BioControl, 2021)

Response of Pseudomonas tolaasii, the causal agent of mushroom brown blotch disease to the volatile compounds produced by endofungal bacteria - Samira Ghasemi; Behrouz Harighi; Mahdi Mojarrab; Abdolbaset Azizi (BioControl, 2021)

Combined effects of elevated CO2 and temperature on multitrophic interactions involving a parasitoid of plant virus vectors - Ana Moreno-Delafuente; Elisa Viñuela; Alberto Fereres; Pilar Medina; Piotr Trębicki (BioControl, 2021)

Competition between Diachasmimorpha kraussii and Fopius arisanus in Bactrocera tryoni: does native parasitoid-host association matter? - Kiran Mahat; Anthony R. Clarke (BioControl, 2021)

Predatory ability of generalist predators on eggs, young nymphs and adults of the invasive Halyomorpha halys in southern Europe - Giacomo Bulgarini; Zaid Badra; Stefano Leonardi; Lara Maistrello (BioControl, 2021)

Bacillus velezensis RC 218 as a biocontrol agent against Fusarium graminearum: effect on penetration, growth and TRI5 expression in wheat spikes - Renata Cantoro; Juan Manuel Palazzini; Nadia Yerkovich; Daniel Julio Miralles; Sofía Noemi Chulze (BioControl, 2021)

Correction to: Life history traits and host-killing rate of Neochrysocharis formosa on Tuta absoluta - P. Guleria; P. L. Sharma; S. C. Verma; R. S. Chandel (BioControl, 2021)

Correction to: Impact of the exotic fall armyworm on larval parasitoids associated with the lepidopteran maize stemborers in Kenya - Bonoukpoè Mawuko Sokame; Julius Obonyo; Enock Mwangangi Sammy; Samira A. Mohamed; Sevgan Subramanian; Dora Chao Kilalo; Gerald Juma; Paul-André Calatayud (BioControl, 2021)

Demographic parameters of the reduviid predator, Rhynocoris marginatus (Reduviidae: Hemiptera) fed on two lepidopterous insect pests - Muhammad Arshad; Muhammad Irfan Ullah; Rashad Rasool Khan; Sana Anjum; Muhammad Tahir; Adeela Shamshad; Muhammad Rizwan (BioControl, 2021)

A predatory mite as potential biological control agent of Diaphorina citri - Milena O. Kalile; André C. Cardoso; Angelo Pallini; Morgana M. Fonseca; Simon L. Elliot; Verônica S. Fialho; Tércio da S. Carvalho; Arne Janssen (BioControl, 2021)

Host specificity and non-target longevity of Calophya lutea and Calophya terebinthifolii, two potential biological control agents of Brazilian peppertree in Florida, USA - Patricia Prade; Carey R. Minteer; Salvador A. Gezan; Vera Carolina Arguijo; Kristen Bowers; James P. Cuda; William A. Overholt (BioControl, 2021)

Impact of the exotic fall armyworm on larval parasitoids associated with the lepidopteran maize stemborers in Kenya - Bonoukpoè Mawuko Sokame; Julius Obonyo; Enock Mwangangi Sammy; Samira A. Mohamed; Sevgan Subramanian; Dora Chao Kilalo; Gerald Juma; Paul-André Calatayud (BioControl, 2021)

The use of artificial habitats increases spider abundance and richness in a vineyard of Argentina - Gabriel Pompozzi; Sofía Copperi; Florencia Fernández Campón; Susana Lagos Silnik; Sol García; Agustina Peralta; Eduardo Albrecht (BioControl, 2021)

Life history study of the mirid Tupiocoris cucurbitaceus feeding on Tuta absoluta eggs: implications for biological control and its combination with inherited sterility - Cynthia L. Cagnotti; Ariel E. Arias; Erika N. Ermantraut; Andrea V. Andorno; Mariana M. Viscarret; Silvia N. López (BioControl, 2021)

The role of overseas genetic surveys to potentially accelerate biological control development for a new Hydrilla verticillata introduction in the USA - Nathan E. Harms; Dean A. Williams; Matthew F. Purcell (BioControl, 2021)

Antimicrobial effect of Bacillus licheniformis HN-5 bacitracin A on rice pathogen Pantoea ananatis - Pengfei Jin; Zheng Tan; Haonan Wang; Wenbo Liu; Weiguo Miao (BioControl, 2021)

Parasitization of the sugarcane aphid, Melanaphis sacchari, by commercially available aphid parasitoids - Nathan H. Mercer; Ricardo T. Bessin; John J. Obrycki (BioControl, 2021)

Summary of classical biological control introductions of entomopathogens and nematodes for insect control - Ann E. Hajek; Sana Gardescu; Italo Delalibera (BioControl, 2021)

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Exotic generalist arthropod biological control agents: need to improve environmental risk assessment to ensure safe use - David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Débora Pires Paula (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Contributions to improve current environmental risk assessment procedures of generalist arthropod biological control agents (GABCAs) in Argentina - Claudia Cédola; María G. Luna; M. Fernanda Achinelly; Norma E. Sánchez (BioControl, 2021)

Non-target effects of the exotic generalist parasitoid wasp Fopius arisanus (Sonan) estimated via competition assays against Doryctobracon areolatus (Szepligeti) on both native and exotic fruit fly hosts - Beatriz A. G. Paranhos; Sonia Poncio; Renata Morelli; Dori E. Nava; Luiz A. N. de Sá; Nicholas C. Manoukis (BioControl, 2021)

Correction to: Risk assessment procedures for biological control agents in New Zealand: two case studies for generalists - Philippa J. Gerard; Barbara I. P. Barratt (BioControl, 2021)

Risk assessment procedures for biological control agents in New Zealand: two case studies for generalists - Philippa J. Gerard; Barbara I. P. Barratt (BioControl, 2021)

Scrutinizing the enemy release hypothesis: population effects of parasitoids on Harmonia axyridis and local host coccinellids in Brazil - Débora P. Paula; Pedro H. B. Togni; Valmir A. Costa; Lucas M. Souza; Alex A. T. C. Sousa; Gustavo M. Tostes; Carmen S. S. Pires; David A. Andow (BioControl, 2021)

Are specialists really safer than generalists for classical biocontrol? - Joseph Michael Taylor; William Emerson Snyder (BioControl, 2021)
Generalists rarely are considered for classical biocontrol because their broad feeding habits are expected to make non-target impacts inevitable. This assumes an increase in overall ecological risk with increasing number of feeding connections. With the goal of inspiring fresh consideration of the safety of exotic biocontrol agents for classical biocontrol, we present a selective review of the impacts of nine particularly-well-studied exotic natural enemies ranging from relative specialists to generalists. Surprisingly, non-target effects could be particularly strong for relative specialists that attacked just a few natives, but were often widespread but weak for the broadest generalists. This appeared to reflect relatively strong apparent competition and density-dependence for the narrow feeders, versus broadly diffuse net effects for the broader feeders. Overall, we suggest a sole focus on specialists in classical biocontrol might be an unreliable means to reduce ecological risk. Additional research is needed to fully compare the net direct and indirect effects of generalists and specialists across food webs, following classical biocontrol releases.

Exploring the potential for novel associations of generalist parasitoids for biological control of invasive woodboring beetles - Xingeng Wang; Xiao-Yi Wang; Marc Kenis; Liang-Ming Cao; Jian J. Duan; Juli R. Gould; Kim A. Hoelmer (BioControl, 2021)

Using qualitative food webs to predict species at risk of indirect effects from a proposed biological control agent - Jacqui H. Todd; Brittany M. Pearce; Barbara I. P. Barratt (BioControl, 2021)

The potential impact of climate change on non-target risks from imported generalist natural enemies and on biological control - James R. Nechols (BioControl, 2021)

A framework for predicting competition between native and exotic hymenopteran parasitoids of lepidopteran larvae using taxonomic collections and species level traits - Zane McGrath; Frances MacDonald; Graham Walker; Darren Ward (BioControl, 2021)

Every generalist biological control agent requires a special risk assessment - Antoon J. M. Loomans (BioControl, 2021)